Tiling Problems on Baumslag-Solitar groups - Nathalie Aubrun; Jarkko Kari (My University, 2022)
We exhibit a weakly aperiodic tile set for Baumslag-Solitar groups, and prove that the domino problem is undecidable on these groups. A consequence of our construction is the existence of an arecursive tile set on Baumslag-Solitar groups.
Machines, Computations and Universality 2013